PRESPEKTIF HUKUM ISLAM TERHADAP TRADISI BELIS DALAM PERKAWINAN ADAT MASYARAKAT DESA KOTODIRUMALI KECAMATAN KEO TENGAH KABUPATEN NAGKEO PROVINSI NUSA TENGGARA TIMUR - Ismail S. Arsyad; Khoirul Asfiyak; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
It is undeniable that marriage is a sacred process wich for some residents in the territory of Indonesia, always includes the practice of traditional customs in it. The community of Kotodirumali Village, Keo Tengah District, Nagekeo Regency, East Nusa Tenggara is no exception who have a special term or designation in the practice of traditional marriage customs known as Belis. This study present problems and perspectives that are tudied in terms of concepts and behavior in the social and cultural world throught qualitative research methods with descriptive research types. The results of the study show that, First, Belis includes the form of offerings from the groom’s family to the brde’s family, also includes all forms of a series of traditional tradition, broadly referred to as Belis. Second, the Belis tradition in marriage does not interfere in the slightest with the legal status of validaty of the marriage. Third, there is no pracitece of the Belis tradition in marriage that deviates, or contradicts the conditions stipulated in Islamic law as a limitation in carrying out all forms of traditional practice. Keywords: Belis, Marriagge, Tradition